2019
DOI: 10.1038/s41562-018-0506-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between adolescent well-being and digital technology use

Abstract: 1The widespread use of digital technologies by young people has spurred speculation that their 2 regular use negatively impacts psychological well-being. Current empirical evidence 3 supporting this idea is largely based on secondary analyses of large-scale social datasets. 4 Though these datasets provide a valuable resource for highly powered investigations, their 5 many variables and observations are often explored with an analytic flexibility that marks small 6 effects as statistically significant, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
746
2
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 994 publications
(811 citation statements)
references
References 34 publications
52
746
2
11
Order By: Relevance
“…Over the last year, other research teams have analyzed these same data (Kreski et al, submitted; Orben & Przybylski, ) and reported similar small initial associations between social media use and depressive symptoms. However, there are two important differences in the recent reporting from these same data.…”
Section: What Do We Currently Know About the Association Between Adolmentioning
confidence: 83%
See 1 more Smart Citation
“…Over the last year, other research teams have analyzed these same data (Kreski et al, submitted; Orben & Przybylski, ) and reported similar small initial associations between social media use and depressive symptoms. However, there are two important differences in the recent reporting from these same data.…”
Section: What Do We Currently Know About the Association Between Adolmentioning
confidence: 83%
“…Similar to findings from systematic reviews and meta‐analyses, the most recent and rigorous large‐scale and preregistered studies have not found strong support for a robust linkage between adolescents’ technology use and well‐being. Using specification curve analysis across three national data sources of adolescents ( N > 350,0000), two based in the United States and one in the UK, Orben and Przybylski () demonstrated that choices related to the specification of variables capturing digital technology use, adolescent well‐being, and confounders can generate a myriad of effect sizes, with the most likely association being exceedingly small and explaining a small portion of the variance in well‐being. More specifically, across their 3,221,225,472 analyses, technology use accounted for less than 1% (0.4%) of the variation in well‐being.…”
Section: What Do We Currently Know About the Association Between Adolmentioning
confidence: 99%
“…separations. Yet, some have argued that using social medial only exacerbates subjective feelings of isolation(118, for review) but see (119,120). Future studies could compare SN/VTA responses to social cues following isolation with and without access to social media.…”
Section: Discussionmentioning
confidence: 99%
“…These popular fears are echoed by internet users who indicate that internet use has impaired their memory and concentration (Näsi & Koivusilta, ) and who feel stressed by the amount of information available online (i.e., experience “information overload”; Horrigan, ). That said, empirical research on the cognitive effects of internet‐based device and internet use has been inconclusive and yielded inconsistent outcomes (e.g., Orben & Przybyzki, ; see also reviews by K. L. Mills, ; Wilmer, Sherman, & Chein, ), and research with young children has rarely been conducted at all. Children are clearly capable of learning from internet‐based devices, just as they are capable of learning from books or television (see Troseth & Strouse, ).…”
Section: Effects On Cognitive Developmentmentioning
confidence: 99%